Valence orbitals and local bond dynamics around N atoms of histidine under X-ray irradiation. Issue 47 (28th November 2017) - Eckert, Sebastian; Niskanen, Johannes; Jay, Raphael M.; Miedema, Piter S.; Fondell, Mattis; Kennedy, Brian; Quevedo, Wilson; Iannuzzi, Marcella; Föhlisch, Alexander
Abstract : Protonation-state dependent coupled electronic and nuclear responses of histidine to N 1s excitations are monitored using RIXS and ab initio MD. Abstract : The valence orbitals of aqueous histidine under basic, neutral and acidic conditions and their X-ray induced transformations have been monitored through N 1s resonant inelastic X-ray scattering. Using density functional ab initio molecular dynamics simulations in the core-hole state within the Z + 1 approximation, core-excitation-induced molecular transformations are quantified. Spectroscopic evidence for a highly directional X-ray-induced local N–H dissociation within the scattering duration is presented for acidic histidine. Our report demonstrates a protonation-state and chemical-environment dependent propensity for a molecular dissociation, which is induced by the absorption of high energy photons. This case study indicates that structural deformations in biomolecules under exposure to ionizing radiation, yielding possible alteration or loss of function, is highly dependent on the physiological state of the molecule upon irradiation.